2022
DOI: 10.1002/adfm.202200428
|View full text |Cite
|
Sign up to set email alerts
|

Toward Direct Growth of Ultra‐Flat Graphene

Abstract: The elimination of wrinkles has become a research hotspot in the realm of the chemical vapor deposition growth of graphene, and there have been reliable routes developed for the scenario of catalytic synthesis on metals. Nonetheless, the transfer‐free growth of graphene over insulating substrates affording ultra‐flatness remains a puzzle. Here, the authors report the direct preparation of ultra‐flat graphene on an economical quartz glass substrate at a wafer level, without any wrinkles and metallic impurities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…But molten glass usually needs to be cooled to make the final graphene film, so the thermal expansion coefficient mismatch between the underlying glass and the upper graphene will cause cracks in the film. 59 Very recently, Liu et al 104 directly grew ultra-flat graphene over wafer-scalable quartz via a strategic synergy between eliminating textured SiO x seeds, boosting growth temperature, and constructing a micro-flow compartment. However, strict process conditions limit its application.…”
Section: Discussionmentioning
confidence: 99%
“…But molten glass usually needs to be cooled to make the final graphene film, so the thermal expansion coefficient mismatch between the underlying glass and the upper graphene will cause cracks in the film. 59 Very recently, Liu et al 104 directly grew ultra-flat graphene over wafer-scalable quartz via a strategic synergy between eliminating textured SiO x seeds, boosting growth temperature, and constructing a micro-flow compartment. However, strict process conditions limit its application.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not found the relevant reports on epitaxial growth of graphene with atomic level flatness on SiC, researchers have achieved atomic level flatness for graphene grown on wafer-scalable quartz, and the average of the measured root mean square roughness values is at 0.338 nm. 65 With the development of technology, it is possible for growth of graphene with atomic level flatness for construction of AlN/graphene/3C-SiC heterostructures. All molecular dynamics simulations are performed using the Large Scale Atomic/Molecular Parallel Simulator (LAMMPS) software package.…”
Section: Models and Methodsmentioning
confidence: 99%
“…[28] Recently, Jiang et al reported the direct growth of ultra-flat graphene on a quartz substrate at a wafer scale without any impurities or wrinkles. [27] Guided by density functional theory (DFT) calculations, the authors revealed that SiO x clusters can be served as heterogeneous seeds to produce isolated multilayer graphene islands. Therefore, a corundum tube with sapphire template instead of the typical quartz tube was employed to circumvent the foreign SiO x contamination, as schematically shown in Figure 2h.…”
Section: Elevated-temperature Growthmentioning
confidence: 99%
“…(k) Variation of the I D /I G ratio of graphene grown by the designed route as a function of growth temperature. (h-k) Reproduced with permission [27]. Copyright 2022, Wiley-VCH.…”
mentioning
confidence: 99%